Moving Out: Mapping Mobile Home Park Closures to Analyze Spatial Patterns of Low‐Income Residential Displacement. (September 2017) - Sullivan, Esther
Abstract : Mobile homes provide the largest source of unsubsidized affordable housing in the United States. However, in mobile home parks residents live at risk of eviction because they rent the land on which their homes are located. This study formulates a methodology to examine the residential turnover and displacement that result from the closure of these parks. I investigate the spatial distribution of closing mobile home parks through ArcGIS modeling of land‐use data for all 1.2 million parcels in the case study region of Houston/Harris County, Texas, from 2002 to 2011. Findings demonstrate that the spatial distribution of closing mobile home parks is clustered along Houston's expanding city limit in areas where affordable housing development is taking place. Beyond providing spatial documentation of the process through which this important source of affordable housing is lost, this study highlights how low‐income housing pressures and urban redevelopment intersect to shape affordable housing in contemporary metropolitan areas.